(untitled) (KYAMC Journal, 2019)
Background: Per vaginal bleeding in the first trimester is a common obstetrical situation ranging from an insignificant episode to life threatening emergency. The major causes are abortion, ectopic and molar pregnancies. Objectives of study: Ultrasonography is playing an increasing role in diagnosis of causes of Per vaginal bleeding in the first. This study was taken up to evaluate the value and utility of ultrasonography in correlation to the clinical findings of Per vaginal bleeding in the first trimester (sonographic evaluation). Materials and Methods: In this prospective study all obstetric cases (with a history of per vaginal bleeding in the first trimester of pregnancy between April, 2015 to November, 2015 (of 8 months) were included. A complete general physical examination including pelvic examination was done to arrive at a clinical diagnosis. Patients were then subjected to ultrasound examination. Clinical and ultrasound findings were correlated. We attempted to indentify the causes of vaginal bleeding occurring in the first trimester by clinical and trans-abdominal sonography and to evaluate the outcomes after instituting appropriate obstetric management. Results: Fatytun of all obstetric cases (200) had the First trimester bleeding (incidence being 21%). The common causes were abortion (85.68%), molar (9.52%) and ectopic (4.80%) pregnancies. The bleeding cases were common in the younger age group 21 to 25years, more in the multigravida within 5 to 8(47%) weeks of gestational age. The commonest cause of bleeding was threatened abortion (28.57%). Early institution of treatment after proper diagnosis has decreased morbidity, at times mortality of women. Ultrasound had not only clinched the diagnosis but also helped in timely management of first trimester vaginal bleeding. Conclusion: Ultrasound is a simple, non-invasive diagnostic modality available in the current day practice to diagnose and to manage first trimester vaginal bleeding. KYAMC Journal Vol. 10, No.-1, April 2019, Page 25-30